Age does not count: resilience of quantity processing in healthy ageing - Lambrechts, Anna; Karolis, Vyacheslav; Garcia, Sara; Obende, Jennifer; Cappelletti, Marinella (Frontiers in Psychology, 2013)
Quantity skills have been extensively studied in terms of their development and pathological decline. Recently, numerosity discrimination has been shown to be remarkably resilient to healthy ageing, but whether processing continuous quantities such as time and space is equally well maintained in ageing participants is not known. Longer exposure to quantity-related problems may progressively refine proficiency in quantity tasks, or alternatively quantity skills may decline with age. In addition, is not known whether the tight relationship between quantity dimensions, as illustrated by interactions between dimensions in discrimination tasks, is preserved in ageing. To address these questions, two experimental paradigms were used in 38 younger and 32 older healthy adults who showed typical age-related decline in attention, executive function and memory tasks. In both groups we first assessed time and space discrimination independently using a two-choice task (i.e. ‘Which of two horizontal lines is longer in duration or extension?’), and found that time and space processing were equally accurate in younger and older participants. In a second paradigm, we assessed the relation between different quantity dimensions which were presented as a dynamic pattern of dots independently changing in duration, spatial extension and numerosity. Younger and older participants again showed a similar profile of interaction between number, surface and duration with some subtle differences in the surface and duration discrimination tasks: older adults showed a greater sensitivity to task-irrelevant information than younger adults in the surface task but lower sensitivity in the duration task. Continuous quantity processing seems therefore resilient to ageing similar to numerosity and to other non-quantity skills like vocabulary or implicit memory; however ageing might affect quantities differently from one another.